2023
DOI: 10.3390/foods12112183
|View full text |Cite
|
Sign up to set email alerts
|

From Industrial Food Waste to Bioactive Ingredients: A Review on the Sustainable Management and Transformation of Plant-Derived Food Waste

Yassine Jaouhari,
F. Travaglia,
L. Giovannelli
et al.

Abstract: According to the United Nations, approximately one-third of the food produced for human consumption is wasted. The actual linear “Take-Make-Dispose” model is nowadays obsolete and uneconomical for societies and the environment, while circular thinking in production systems and its effective adoption offers new opportunities and benefits. Following the “Waste Framework Directive” (2008/98/CE), the European Green Deal, and the actual Circular Economy Action Plan, when prevention is not possible, recovering an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…The European circular system is able to achieve a potential reduction of 71% in agricultural land use and 29% per capita in GHG emissions while still producing sufficient healthy foods. Other studies have shown that food waste and byproducts can be managed and valorized through a circular economic system [45,55]. In a circular economic system, food byproducts can safely be upcycled and reused for human consumption and/or industrial applications.…”
Section: Sustainable Grain Processing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The European circular system is able to achieve a potential reduction of 71% in agricultural land use and 29% per capita in GHG emissions while still producing sufficient healthy foods. Other studies have shown that food waste and byproducts can be managed and valorized through a circular economic system [45,55]. In a circular economic system, food byproducts can safely be upcycled and reused for human consumption and/or industrial applications.…”
Section: Sustainable Grain Processing Systemmentioning
confidence: 99%
“…A number of bioconversion methods using either enzymes or microorganisms, along with other technologies such as microencapsulation, supercritical extraction, microwave-assisted extraction, ultrasound, and pulse electric field, could be utilized for efficient recovery and product quality. Details about the valorization of byproducts and waste from cereal processing and plant-derived food waste into valuable ingredients and products have been previously discussed in recent review articles [45,55].…”
Section: Sustainable Grain Processing Systemmentioning
confidence: 99%
“…When in 2015 the European Commission adopted the first Circular Economy Action Plan, food waste management was identified as a priority [54]. The depletion of nonrenewable resources and the need for better management of post-production waste were identified as a criterion for sustainable production.…”
Section: Food Waste As Sustainable Raw Materialsmentioning
confidence: 99%
“…It is important to note that, although waste is considered a negative result of a process, co-products can have a positive impact on the food supply chain, provided they are properly managed [28]. It is estimated that a reduction in agro-industrial waste of between 30 and 50% could increase the available food supply by at least 15% with the appropriate use of these fractions [29].…”
Section: The Importance Of Converting Fruit Agro-industry Waste Into ...mentioning
confidence: 99%